Land-based tax capacity and tax effort of the State Governments in Peninsular Malaysia: a Representative Revenue System (RRS) approach - Ahmad Zafarullah Abdul Jalil, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2011)
The Auditor General Report 2004 revealed that seven out of 13 states in Malaysia are facing dire financial difficulties to the extent of being qualified as at the verge of bankruptcy. One of the solutions proposed would be to devolve more tax responsibilities to the state governments. However, some authors have argued that the Malaysian state governments have not been using their tax base efficiently and the devolution of more tax responsibilities towards them will only result in more inefficiency. It is thus important to gauge the fiscal effort exerted by the state governments before any attempts being made towards increasing tax responsibilities of the state governments. The main objective of this article is to measure the fiscal effort and capacity of the state governments in Peninsular Malaysia. In order to achieve this, we will use the Representative Revenue System (RRS)/ Representative Tax System (RTS) approach. This paper will discuss the preliminary findings of the research using the 2008 data. Our results show that more-developed states tend to have higher index of tax effort compared to the less-developed ones. It is also shown that state governments with high fiscal effort are in a relatively better fiscal position. However, tax arrears do not seem to correlate with the level of tax effort.